Gray’s (1845) Heteronota kendallii and the mysterious Mr. Kendall. - Indraneil, Das; MARTYN E., Y. LOW (Society for the Study of Amphibians and Reptiles, 2024)
This note provides an argument that the eponym of the Bornean gecko Cnemaspis kendallii was the explorer and hydrographer, Edward Nicholas Kendall (1800–1845). Kendall was an assistant to John Richardson (1787–1865), naturalist, and physician in the expedition to the Mackenzie River Delta in Canada, between 1825 to 1827, and died prematurely. While Richardson served as the namesake for a variety of squamates that were described by John Gray at the British Museum, it is plausible that the former requested the name of Kendall be honored through the naming of a new species.